The professional challenges of the Educational Inspection for the application of the LOE - Uruñuela Nájera, Pedro María (Avances en Supervisión Educativa, 2008)
Traditionally, the definition and description of Inspectorate of Education itself and its duties has been made under two main streams, apparently contradictory: considering the Inspectorate as a body of managers and supporters of the Educational System, or, on the contrary, regarding the Inspectorate as a group of agents who stimulate educational changes, general improvement and development of highquality standards in Education. From the first point of view, inspectors are encouraged to supervise the fulfilment of all laws and regulations in force. From the second outlook, they are recommended to take priority on the analysis of opportunities inside the Educational System, on the detection of new social needs of teachers and students as well as on the active cooperation in search of the most suitable solutions to these new needs.